1987
DOI: 10.1007/bf02555125
|View full text |Cite
|
Sign up to set email alerts
|

Compositional analysis of collagen from patients with diverse forms of osteogenesis imperfecta

Abstract: Collagen was extracted by pepsin treatment from various tissues and skin fibroblasts of 23 patients belonging to different types of osteogenesis imperfecta (OI), and characterized by molecular sieve and ion exchange chromatography, gel electrophoresis, and amino acid analysis. We found an elevated collagen III/I ratio in the skin of one patient with OI type I but almost normal values in skin fibroblasts of two other patients of this OI type. Five patients with OI type II had a normal collagen III/I ratio in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…The presence of collagen I11 and increased amounts of collagen V in bone has been described for lethal cases of 01 type I1 and also, more recently for 01 types I11 and IV [9,21,22]. This study confirms these results and provides evidence that even the mild 0 1 type I patients have levels of collagen TI1 and V in bone compacta comparable to those of the more severely affected cases.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The presence of collagen I11 and increased amounts of collagen V in bone has been described for lethal cases of 01 type I1 and also, more recently for 01 types I11 and IV [9,21,22]. This study confirms these results and provides evidence that even the mild 0 1 type I patients have levels of collagen TI1 and V in bone compacta comparable to those of the more severely affected cases.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, it should be noted that the substantial decrease in fracture rate in patients with 01 I11 and IV as they grow older is hard to reconcile with the steady expression of a mutated collagen gene [7]. In this context, not only collagen I but also collagen I11 and V were found to be overhydroxylated in 01 which is not consistent with a single gene defect [8,9]. Furthermore, there is experimental evidence to support the notion that during development, the degree of hydroxylation of lysyl residues as well as their glycosylation is regulated and that this process is defective in the lethal perinatal01 type I1 [lo].…”
Section: Introductionmentioning
confidence: 99%
“…The co-occurrence of collagen abnormalities with skeletal architectural defects in 01 (Bonadio and Byers, 1985;Kirsch et al, 1987;Royce et al, 1988) raises the possibility that collagen structure can influence the way that bone detects and responds to its mechanical environment. Using SEM, Teitelbaum et al (1974) found defects in the ability of collagen fibrils to aggregate into fiber bundles of normal thickness.…”
Section: Osteogenesis Imperfecta: a Disorder That Decreases Activatiomentioning
confidence: 99%
“…44,45 Collagen folding starts from the C-terminus, and careful analysis indicated overmodification to be present only N-terminal to the mutation site, 1,46 consistent with the mutation leading to delayed folding. It has been suggested that OI may fall into the category of protein folding diseases, which includes Alzheimer's disease and the most common type of cystic fibrosis.…”
Section: Gly Missense Mutations and Folding Of Oi Collagensmentioning
confidence: 99%